Sweet taste preference status and its association with preference for the four basic taste modalities of various food - Marina Abdul Manaf,; Nurul Nurain Mohamad Zazali,; Siti Anis Izyani Abdul Wahid, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Sweetness preference is a complex sensation involving multidisciplinary fields and it has been studied extensively. However, there is still limited information on how the status of the sweet preference of individuals influences their preference for other taste modalities. Thus, this study was conducted to observe the difference in the preference for various types of foods based on the four taste modalities, with sweet taste preference (STP) status. This cross-sectional study involved 156 university students in Kelantan, Malaysia. The preference test of tea drink sweetness was determined using the hedonic test. Subjects were grouped into low, medium, and high STP according to their STP level. The preference for the taste modalities of different food groups was determined by using a questionnaire. The results indicated that the majority of subjects were in the medium STP group. Foods categorized under the sweet taste group were mostly correlated with the STP status, followed by salty and sour foods. There was no correlation (p>0.05) between STP status and bitter foods. This result agrees with the principal component analysis (PCA). Two factors were extracted from PCA, in which the first factor explained 56.41% and the second factor explained 20.45% of the variance. Sweetness is related to foods that are categorized under salty and sour tastes, but not related to bitter tastes. This study shows that sweetness preference status is associated with preference for two other basic tastes. The high STP subject not only prefers sweet foods but also favors foods from salty and sour groups.